First characterization and risk assessment of microplastics in the endangered Indus River dolphin (Platanista minor): Implications for conservation strategies - Ali, Ahsaan; Sonne, Christian; Aslam, Mehmood; Ali, Imran; Hussain, Sajjad; Qadir, Abdul; Sukhera, Shazia; Ali, Hassan; Ahmad, Sajid Rashid; Yang, Guang (PLOS ONE, 2025)
Microplastic (MP) pollution has become a global environmental concern due to its ubiquitous presence and potential threats to ecosystems. Cetaceans, as top predators, have served as sentinel species for monitoring ecosystem changes and as flagship species for establishing environmental conservation strategies. Here, we investigated MPs for the first time in the complete gastrointestinal tract of five individuals of an endangered Indus River dolphins (Platanista minor) stranded along the Indus River from 2019−2022. MPs were detected from all examined specimens with an average of 286.4 ± 109.1 MPs per individual, indicating the potential pathways for the accumulation of MPs due to prey consumption and unintentional ingestion during food uptake in Indus River dolphin. The properties of MPs demonstrated that the most prevalent shapes were fibers, with sizes mostly ranging from 5 mm-300µm. Polyethylene terephthalate (PET) was the predominant composition identified via FT-IR spectroscopy. Moreover, the prevalence of MPs observed in the small intestine was higher than in other parts due to length and structure. This is the first study to highlight the ecological risks posed by MP polymers through a polymer risk assessment (H) showing medium (Level III) to high risks (Level IV) to Indus River dolphins. This study represents the first baseline assessment of MPs pollution caused by anthropogenic activities and offers valuable insights for the conservation of this endangered freshwater species. Our results emphasize the need for further ecotoxicological studies to better understand the potential impacts of MPs in this endangered species.